Baby signing time! Vol. 4, Let's be friends [videorecording (DVD)]. - Coleman, Rachel (Baby signing time!, 2008)
Join Hopkins, Alex, and Leah as they learn everyday signs such as friends, emotions, fruits, vegetables, opposites, and many more. Songs include Can you feel it?, Toy box, Show me a sign, and That tastes good.